In Silico Design of Multiplex PCR Primers for the Detection of Foodborne Pathogens in Fermented Shrimp Paste (Terasi) from Lombok Island: In Silico PCR and Primer Verification - Unsunnidhal, Lalu; Perdhana, Firman Fajar; Ariyana, Mutia Devi (Westscience Press, 2025)
Fermented shrimp paste (terasi) is a traditional food product produced by micro, small, and medium enterprises (MSMEs) in Lombok Island, Indonesia. Due to its fermentation and handling processes, terasi is susceptible to contamination by foodborne pathogens. The Indonesian Food and Drug Authority has identified specific bacterial pathogens that pose a risk of contamination in shrimp paste, necessitating accurate and efficient detection methods. Molecular detection using polymerase chain reaction (PCR) is known for its high specificity and sensitivity, as well as its rapid processing time and cost-effectiveness. However, conventional PCR can only detect a single target pathogen in one reaction, limiting its efficiency in screening multiple contaminants simultaneously. This study aims to design and optimize Multiplex PCR primers for detecting multiple foodborne pathogens in terasi through an in-silico approach, followed by In Silico PCR verification to assess primer specificity and efficiency. Target pathogens include Salmonella spp., Staphylococcus aureus and Vibrio cholerae. DNA target sequences were retrieved from the National Center for Biotechnology Information (NCBI) database, and primer design was conducted using Primer3Plus software. The designed primer sets were validated using Primer-BLAST (NCBI), and in-silico PCR was performed to verify amplification efficiency and specificity. The designed primer set has been successfully obtained and evaluated using In Silico PCR and Primer-BLAST (NCBI), confirming its specificity to the target genes. These results demonstrate that the primers can be effectively used as a molecular detection tool for foodborne pathogens. The optimized conditions and validated primer set are expected to contribute to molecular-based food safety detection methods, particularly for Indonesian fermented food products.